2015
DOI: 10.1039/c5ra02112j
|View full text |Cite
|
Sign up to set email alerts
|

Platinum nanoparticles supported on N-doped carbon nanotubes for the selective oxidation of glycerol to glyceric acid in a base-free aqueous solution

Abstract: Selective oxidation of glycerol was carried out over Pt catalysts supported on nitrogen-doped carbon nanotubes (Pt/N-CNTs) with molecular oxygen under atmospheric pressure in base-free aqueous solution. The N-CNTs were readily synthesized through a catalyst-free approach of annealing the mixture of CNTs and melamine. Results of X-ray diffraction, nitrogen absorption, and Raman spectroscopy confirmed that the tubular structure of CNTs was intact during annealing. Analyses of transmission electron microscopy, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 54 publications
(116 reference statements)
1
62
0
2
Order By: Relevance
“…The incorporation of basic sites in catalyst support as solid base additives to replace liquid alkalis is believed to tune surface electron reconfigurations of metal for promoting oxidation reactions. Pt nanoparticles immobilized on anion exchange resins, nitrogen doped carbon nanotubes (entry#10 in Table ) and mesoporous carbon nitride (Figure (a), entry#8 in Table ) show synergistic activity during glycerol oxidation to glyceric acid. Nitrogen‐doped carbon materials are found to accelerate the activation of O−H bond in glycerol molecules to alkoxide .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of basic sites in catalyst support as solid base additives to replace liquid alkalis is believed to tune surface electron reconfigurations of metal for promoting oxidation reactions. Pt nanoparticles immobilized on anion exchange resins, nitrogen doped carbon nanotubes (entry#10 in Table ) and mesoporous carbon nitride (Figure (a), entry#8 in Table ) show synergistic activity during glycerol oxidation to glyceric acid. Nitrogen‐doped carbon materials are found to accelerate the activation of O−H bond in glycerol molecules to alkoxide .…”
Section: Figurementioning
confidence: 99%
“…Pt nanoparticles immobilized on anion exchange resins, nitrogen doped carbon nanotubes (entry#10 in Table ) and mesoporous carbon nitride (Figure (a), entry#8 in Table ) show synergistic activity during glycerol oxidation to glyceric acid. Nitrogen‐doped carbon materials are found to accelerate the activation of O−H bond in glycerol molecules to alkoxide . Electron donating groups can anchor Pt particles effectively while promoting nucleophilic attack on terminal carbon and activation of C−H bond in glycerol molecules.…”
Section: Figurementioning
confidence: 99%
“…There are many reports on the oxidation of glycerol over Pt‐ and Pd‐based anode catalysts in both acidic and basic solutions. Pt acts as a universal catalyst in the oxidation of small organic molecules . Nevertheless, this metal is expensive, because only small amounts of Pt are available in the earth's crust.…”
Section: Figurementioning
confidence: 99%
“…Chen et al reported oxidation of glycerol over reusable Pt catalysts supported on nitrogen-doped carbon nanotubes (Pt/N-CNTs) with 0.1 MPa O2 at 333 K in base-free aqueous solution formed glyceric acid with 43 % selectivity and 51 % conversion 75) . TPD analyses indicated that the surface of the CNTs had basic sites originating from doped nitrogen atoms.…”
Section: Oxidative Transformations Of Glycerolmentioning
confidence: 99%